Pre-applied bonded waterproofing membranes: A review of the history and state-of-the-art in Europe and North America. (16th August 2021) - Heinlein, Ulli; Thienel, Karl-Christian; Freimann, Thomas
Highlights: Pre-applied bonded waterproofing membranes are reviewed. State-of-the-art properties, applications, and national regulations are presented. Latest investigations and further research needs are summarized. Insight into the history and the significance on the market is given. Abstract: Since the end of the 20th century, below-grade concrete structures can be waterproofed with sheet membranes in a pre-application process. The waterproofing membranes are installed before concrete placement, e.g., directly on a soil retention system and interact with the subsequently poured fresh concrete, thus forming an adhesive and waterproof bond. The market for this construction method is currently growing, which is why characteristics, mechanisms, and international regulations in place are reviewed. Moreover, the history of pre-applied bonded membranes is presented, based on a product and patent research. Also, recently conducted investigations and an outlook on further research needs is given.